Do more faster : techstars lessons to accelerate your startup 2nd edition - Feld, Brad (Gildan Audio, 2019)
Refreshed, updated, and expanded. Do More Faster provides time-tested advice, tips, and experiences by founders and mentors of Techstars to help entrepreneurs succeed! David Cohen and Brad Feld, leading advocates for entrepreneurs and startups, team up to provide first-time entrepreneurs with the tools, insights, and experiences to help them do more faster. The authors share their decades of experience working with thousands of startup founders and have enlisted the advice of dozens of Techstars startup founders and mentors. Contributors include Tim Ferriss, Eric Ries, Matt Mullenweg (WordPress), Isaac Saldana (SendGrid), and other successful entrepreneurs. Cofounders of Techstars, the worldwide network that helps entrepreneurs succeed, Cohen and Feld recognize the daunting task of creating a sustainable business and have seen first-hand the common mistakes first-time entrepreneurs make over and over. The authors take the complexity and uncertainty of starting a business and distill the critical factors into seven themes: Ideas and Vision, People, Working Effectively, Product, Fundraising, Legal and Structure, and Work and Life Harmony. They share their hard-won successes, failures, and advice for anyone with an idea who wants to create a business.